ҚАЗІРГІ ДІНИ СТИЛЬ ЖӘНЕ ИСЛАМ ЛЕКСИКАСЫН ОРЫС ТІЛІНЕ АУДАРУ МӘСЕЛЕЛЕРІ (Eurasian Journal of Philology Science and Education, 2015)
The article is devoted to the study of a modern religious style in the system of the functional-stylistic and culturalhistorical paradigms of language. It discusses the different approaches of scientists to study this phenomenon, as well as specific examples of the semantic-stylistic processes associatedwith the rehabilitation of linguistic elements, caught on the periphery of the language. The Islamic religious vocabulary translation ways from the Kazakh language into Russian languag and the ability to transfer the equivalent in semanticsChurch Slavonics are analyzed in the article.